ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERUSAHAAN MELAKUKAN AUDITOR SWITCHING SECARA VOLUNTARY - Novia Retno Astrini; Dul Muid (Diponegoro Journal of Accounting, 2013)
Auditor independence is the key for the auditor when they performing their duties. To avoid the unwanted things related the auditor independence, the company should make an action to do mandatory auditor switching. But, there are several company that do a voluntary auditor switching. This study aim to find empirical evidence on the factor affect the manufacturing companies listed on BEI such as reputation, management changes, financial distress, accountant opinion, and audit tenure to do a voluntary auditor switching. The data used in this research are the companies listed on BEI during 2009-2012. A total of 32 manufacturing companies are used as the sample. The results of this research indicate that the independent variables that affect the voluntary auditor switching is audit tenure. While the other independent variables such as auditor reputation, management changes, financial distress, and accountant opinion does not affect the voluntary auditor switching.